Improving impact of research papers. (June 2016) - Linton, Jonathan D.
Abstract: This editorial aims to assist authors in maximizing the impact of their work. While the editorial is written specifically for the journal Technovation, many items of advice are equally applicable to other publishing outlets. While the value of any article is its unique core contribution, the best way to present an article's core value is quite consistent and is the focus of this editorial.